Views Of Self-Demand And Social Competition In Young People In The Educational Process - Xamzaeva Bekzod Ibragimovich (The American Journal of Social Science and Education Innovations, 2021)
This article is positive in expanding the benefits created by the author to increase the knowledge of young people, on the one hand it increases the competitiveness of a student who graduated from a particular university, on the other hand he makes a worthy contribution to raising the prestige of that institution. The impact of youth education strategies, that is, on their transition to an institutional state and the improvement of their life plans through their level of education, has been analyzed.